2007
DOI: 10.1007/s10209-007-0081-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-formal therapy and learning potentials through human gesture synchronised to robotic gesture

Abstract: Children with severe physical disabilities have limited possibilities for joyful experiences and interactive play. Physical training and therapy to improve such opportunities for these children is often enduring, tedious and boring through repetition-and this is often the case for both patient and the facilitator or therapist. The aim of the study reported in this paper was to explore how children with a severe physical disability could use an easily accessible robotic device that enabled control of projected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
2
8
1
Order By: Relevance
“…[7] extends this theory by emphasizing that the introduction of mediating tools created an imbalance in the systemic organization of the actions, which enhanced changed action patterns. Similarly, findings from the studies presented in [5,6,8,9] demonstrated individual variation in action cycles. For example, one of the participant in [5] showed through his facial expressions that he went through different phases of interaction where intense concentration was balanced by relaxation, yet all aspects of the physical movements were intentional within his limits.…”
Section: Transformation Of Actionssupporting
confidence: 60%
See 1 more Smart Citation
“…[7] extends this theory by emphasizing that the introduction of mediating tools created an imbalance in the systemic organization of the actions, which enhanced changed action patterns. Similarly, findings from the studies presented in [5,6,8,9] demonstrated individual variation in action cycles. For example, one of the participant in [5] showed through his facial expressions that he went through different phases of interaction where intense concentration was balanced by relaxation, yet all aspects of the physical movements were intentional within his limits.…”
Section: Transformation Of Actionssupporting
confidence: 60%
“…It has been shown in previous research that explorations are involved in the mastery of tools and in the growth of competence [3,4,5,6]. In the study presented in [6], the children (with severe special needs) were dynamically exploring what was occurring as a result of their empowered control. Their discovery of the interactive space involved range, speed, and directional variation of their gestures.…”
Section: Ludic Engagment Designsmentioning
confidence: 95%
“…Theoretical/Methodological Rationale (a) Non-formal therapy and learning The development of this play scenario was based on concepts taken from the non-formal therapy and learning methodology where learning emerges from play situations that offer resources for joyful experiences and expressive interactions, and where the child is empowered to control feedback stimuli [43].…”
Section: Tactile Play Scenario Ts01-"make It Smile"-a Cause and Effecmentioning
confidence: 99%
“…Liu, Conn, Sarkar and Stone It seems likely that robotics will have much to offer in the field of technology to assist learning, and indeed to assist daily living, although the latter is beyond the scope of this paper. The availability of gesturing technologies led to exploratory work with learners with a motor disability who were able to interact with a multimedia robotic device (Petersson & Brooks 2007). More recently, Standen et al (2011) have evaluated the use of the Wii Nunchuk as an alternative assistive device for people with physical and intellectual disabilities who normally use switches to interact with computer software.…”
Section: Technology Uses To Assist Learningmentioning
confidence: 99%